Girls with Premature Thelarche Younger than 3 Years of Age May Have Stimulated Luteinizing Hormone Greater than 10 IU/L - Gülcan Seymen Karabulut; Müge Atar; Filiz Mine Çizmecioğlu Jones; Şükrü Hatun (Galenos Yayincilik, 2020)
Objective:Premature thelarche (PT) is defined as isolated breast development in girls before eight years of age. Gonadotropin-releasing hormone (GnRH) stimulation test is sometimes used to distinguish between PT and central precocious puberty (CPP), although the interpretation of the test at early ages is challenging. The objective of this study was to determine the follicle stimulating hormone (FSH) and luteinizing hormone (LH) responses to GnRH stimulation in girls with PT below 3 years of age.Methods:A standardized GnRH stimulation test, bone age and pelvic ultrasound were evaluated and those without pubertal progression after a minimum of one-year follow up were included in the study.Results:On GnRH stimulation test, the median (range) baseline LH was 0.29 (0.10-0.74) IU/L, baseline FSH was 4.96 (3.18-7.05) mIU/mL, and the peak median LH was 5.75 (3.31-8.58) IU/L with the peak mean±standard deviation FSH was 40.38±20.37 mIU/mL. Among the patients, 33.3% (n=10) had baseline LH >0.3 IU/L, 67% (n=20) had peak LH >5 IU/l and 16.6% (n=5) >10 IU/L. The mean peak LH/FSH ratio was 0.17±0.09 and was ≤0.43 in all participants.Conclusion:Although consensus statements usually define baseline LH >0.3-0.5 IU/L, peak LH >5 IU/L, and LH/FSH ratios >0.66-1.0 as diagnostic cut-offs for CPP, in children below 3 years of age, the baseline and peak LH values may be similar to pubertal values, possibly due to mini-puberty. A dominant FSH response on GnRH stimulation test is more valuable than the peak LH response in the diagnosis of PT.